Multiple Scalp Lesions in a Patient with Keratitis, Ichthyosis and Deafness Syndrome Mimicking Metastatic Squamous Cell Carcinoma on 18F-FDG PET/CT - Kleis, Margit A. (Radiol Case Rep, 2016)
We report the case of a 17-year-old girl with keratitis, ichthyosis, and deafness (KID) syndrome. As a complication of her KID syndrome she developed squamous cell carcinoma at the left index finger. Additional clinical features were multiple soft tissue lesions over the scalp mimicking metastatic disease on 18F-FDG PET/CT. To our knowledge, this is the first case report about the uptake pattern of KID syndrome associated skin lesions on whole body PET/CT with 18F-FDG.